PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN DAN NILAI PASAR PERUSAHAAN SEKTOR KEUANGAN DI INDONESIA - Theresia Margaretha Oktavia; Fuad Fuad (Diponegoro Journal of Accounting, 2015)
For the financial sector companies managing intellectual capital is important because this sector should invest for the development of human capital, organizational processes, and corporate knowledge base in order to make a competitive advantage sustainable and durable. This study aimed to examine the effect of intellectual capital on financial performance and market value of financial sector companies.By  using  multiple  linear  regression  analysis,  this  study  examines  the  effect  of  IC  as measured by value added intellectual capital efficiency (VAIC) and it’s three components (capital employed, human capital and structural capital) on financial performance (ROA, ROE, and GR) and market value of the company (MtBV). The data used are secondary data obtained from 159 financial sector companies listed in Indonesia Stock Exchange in 2011-2013.The findings show that there is a positive significant effect of the intellectual capital (VAIC) on financial performance (ROE and ROA) and there is no effect of intellectual capital on the market value (MVtBV). VACA affect positively financial performance (ROE) and market value. VAHU has positive significant effect on financial performance (ROE and ROA) and does not   have a significant effect on the market value. STVA has positive significant effect on the market value and does not have a significant effect on financial performance. The contribution of IC to the financial performance (ROE) and market value differs by industries.